Psychological strategies used by competitive gymnasts to overcome the fear of injury - Magyar, T. M.; Chase, M. A. (Technique, 1996)
Based on the findings of the study, it seems that if a gymnast wants to overcome the fear of being injured, it would be beneficial if she learned how to use psychological skills. Psychological skills training is an educational program designed to develop cognitive strategies in combination with physical skill development to enhance gymnastics performance and one`s overall experience in the sport (Weiss, 1991). Three basic strategies that are a foundation of a solid psychological skills program are relaxation, imagery, and positive self-talk. The finding from this study also revealed that coaches play an integral role in helping the gymnasts overcome their fears of being injured. The girls in this gymclub trusted their coaches a great deal, especially when attempting a new sill or one with high difficulty. The coaches support goes beyond the physical presence of spotting the gymnasts to help them advance physically in the level of difficulty of a skill. They also help the gymnasts mentally, and assist them in overcoming mental barriers such as fear of injury. Therefore, coaches need to be accurate in their feedback and judgment of the gymnasts abilities to progress to the higher levels. Based on these responses, it is apparent the gymnasts in this study exposed to such training used the subsequent skills to combat their fears of being injured. In order to decrease the fear of injury, both the athlete and coach must work together to incorporate psychological skills training into everyday training regimens. The significance of the coaches role also needs to be emphasized during practice and competition to help the gymnast overcome adversity.